The Difference Place Makes: Regional Legislative Approaches to Territories of Traditional Nature Use in the Russian North - Fondahl, Gail; Parlato, Nicholas; Filippova, Viktoriya; Savvinova, Antonina (Arctic Review on Law and Politics, 2021)
Indigenous northerners’ rights in the Russian Federation are legally protected at a range of levels (federal, regional, municipal), and by a diversity of types of legal acts (laws, decrees, orders, provisions). Within the complex structure of Russian federalism, the country’s regional governments elaborate upon federal laws in diverse ways and at different times. This article explores regional approaches to legislating one law on Indigenous rights, that of “Territory of Traditional Nature-Use” (territoriya traditsionnogo prirodopol’zovaniya) (TTP), identified by Indigenous leaders as the most important legal-territorial designation for protecting Indigenous livelihoods and cultures. While it is well known that legal strategies of the Russian state toward Indigenous territorial rights differ markedly from those of other Circumpolar countries, less appreciated are the ways in which these vary across space within Russia. We assert that the spatial informs the legal, documenting several illustrative approaches that regions have taken in legislating TTPs. In doing so, we demonstrate how a federal law initiative is interpreted and reimagined in place, giving rise to the potential for substantively different spatial outcomes for Indigenous persons and peoples seeking to actualize their rights to territory.